Long term monitoring of rainwater harvesting tanks: Is multi‐years management possible in crystalline South Indian aquifers?. Issue 12 (12th December 2022) - Boisson, Alexandre; Villesseche, David; Selles, Adrien; Alazard, Marina; Chandra, Subash; Ferrant, Sylvain; Maréchal, Jean‐Christophe
Abstract: In semi‐arid regions as in India, where agriculture relies on groundwater abstraction, increase of water resources availability through managed aquifer recharge (MAR) or rainwater harvesting (RWH) is often perceived as a major solution. Studies on these structures' efficiency exists but despite the interest, limited information is available on the temporal variation of their replenishment. In a monsoon driven climate, the inter‐annual variations are crucial to assess the potential of water storage and multi‐year management especially for these structures. Here, we aim at developing a methodology to reconstruct water storage of RWH tanks to further improve our understanding on long term efficiency and multi‐years drought management. To tackle this issue, long‐term monitoring of a RWH tank located in Telangana in Southern India is achieved by a combination of field monitoring over 2 years (tanks surface and water levels) and a daily water balance compared to LANDSAT measurements of the tank area. The procedure allows reconstructing the tank filling dynamic over a 14‐years period at a daily time step and show the extreme variability of the tank filling level. During this period, the yearly maximum tank volume ranges from 8650 to ~200 000 m 3 . On the 14‐years period, the tank reach its maximum capacity only once and, for 1/3 of the time, yearly maximum replenishment is below 15% of its capacity. The surface water availability remains limited in time since the tank dries‐up annually, except for 2 years. However, water percolation to the aquifer is slightly enhanced for some years. During this monitoring period, very few extreme raining events (6) contribute for more than 50% of the collected volume. This observation highlights (1) the dependency of the structure to extreme storm events, (2) the limited capacity for a multi‐year's management and (3) the farmers vulnerability to successive droughts. Abstract : Measurements: (a) Evolution of water levels in the tank versus rainfall; b) maximum water extent in tank are after the 2012 monsoon and 08/08/2012, dark red and 2013 monsoon (30/10/2013, light red). (c) Tank area evolution estimated through computed water balance, remote sensing data and GPS tracking. Shaded grey represent the uncertainty.